The Effectiveness of Digital Media in Improving Adolescent Health Literacy about the Dangers of Smoking: Literature Review - Isah Fitriani; Sitti Nur Djannah; Heni Trisnowati (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: The prevalence of smoking in adolescents is still relatively high both in the world and in Indonesia. Not only teenage boys, but adolescent girls also consume cigarettes. The 2022 National Socio-Economic Survey noted that 37.49% of children at that age smoked more than 60 cigarettes every week. In fact, adolescent health is a long-term investment that needs to be considered considering its urgency as the nation's next generation. In this case, the emergence of technology has the potential to provide measurable innovative interventions in tobacco control through health promotion media. Objective: This study aims to explore articles that discuss the effectiveness of digital media in increasing health literacy, the dangers of smoking in adolescents seen from the variables that have changed. Method: The method used is a literature review by analyzing articles relevant to the research topic with a publication range of 2019-2024. The databases used are Pubmed, DOAJ, and Google scholar with the keywords